PERBEDAAN KECERDASAN SPASIAL ANTARA SISWA LAKI-LAKI DAN SISWA PEREMPUAN KELAS X SMA YPK MEDAN PADA MATERI GEOMETRI - Suci Dahlya Narpila (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
This research stems from the writer’s curiosity about the difference of spatial intelligence between male and female students in SMA YPK Medan. The purpose of this research was to describe data of the difference of spatial intelligence between male and female students. This research was a comparative causal research. The sample of this research were 65 students of SMA YPK Medan, which consisted of 32 were female students and 33 were male students. Data to be collected in this research was the data of student’s spatial intelligence which were grouped, i.e. the data of female students spatial intelligence and the data of male students spatial intelligence. The data were collected then analyzed by independent samples t-test in SPSS program. From result of SPSS obtained data Sig 0,02 < 0,05. Based on the result of data analysis could be conluded that there were the difference of spatial intelligence between male and female students in SMA YPK Medan. The average spatial intelligence of male students were 27,06 higher than the average spatial intelligence of female students were 26,76. Then it could be concluded the spatial intelligence of male students better than the spatial intelligence of female students.